2014
DOI: 10.1155/2014/456386
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of PPARδin Type-1-Like Diabetic Rat for Higher Mortality after Spinal Cord Injury

Abstract: Changes in the peroxisome proliferator-activated receptors-δ (PPARδ) expression in rats after spinal cord injury (SCI) have been previously reported. Diabetic animals show a higher mortality after SCI. However, the relationship between the progress of diabetes and PPARδ in SCI remains unknown. In the present study, we used compressive SCI in streptozotocin-(STZ-) induced diabetic rats. GW0742, a PPARδ agonist, was used to evaluate its merit in STZ rats after SCI. Changes in PPARδ expression were detected by We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Therefore, we provided evidence that morin can activate the I‐R linked to PLC activation, which may increase the intracellular calcium content for insulin secretion in MIN6 cells. These results are similar to the effects of other agonists, such as allantoin or canavanine . Moreover, activation of PLC will generate IP3 in addition to diacylglycerol (DAG), which activates protein kinase C (PKC), and Gαq could be involved in the activation of PLC/PKC‐dependent pathways, similar to the effect of glucagon‐like peptide‐1 (GLP‐1) on insulin secretion .…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Therefore, we provided evidence that morin can activate the I‐R linked to PLC activation, which may increase the intracellular calcium content for insulin secretion in MIN6 cells. These results are similar to the effects of other agonists, such as allantoin or canavanine . Moreover, activation of PLC will generate IP3 in addition to diacylglycerol (DAG), which activates protein kinase C (PKC), and Gαq could be involved in the activation of PLC/PKC‐dependent pathways, similar to the effect of glucagon‐like peptide‐1 (GLP‐1) on insulin secretion .…”
Section: Discussionsupporting
confidence: 53%
“…The blots were then transferred to a polyvinyl difluoride membrane. After blocking with 10% skim milk for 1 hour, the blots were developed using a primary antibody specific for NISCH, as described previously . The membranes were then incubated with secondary antibodies for an additional 3 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 Additionally, the activation of PPARδ is helpful to improve the injury from SCI in diabetic rats. 14 The present study is thus designed to investigate the therapeutic potential of telmisartan in SCI using animal model as pre-clinical evidence.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that PPAR participates in the pathogenesis of diseases, such as diabetes and SCI (24,25). In addition, it has been observed that the decrease of PPAR-δ expression in the spinal cord of streptozotocin (STZ)-diabetic rats may explain the higher mortality rate observed following SCI in STZ-diabetic rats (26). Thus, activation of PPAR-δ may reduce the severity of SCI, and PPAR-δ may be a target for therapy in SCI patients (27).…”
Section: Discussionmentioning
confidence: 99%